Water undersaturated mantle plume volcanism on present‐day Mars. (6th September 2016) - Kiefer, Walter S.; Li, Qingsong
Abstract: Based on meteorite evidence, the present‐day Martian mantle has a combined abundance of up to a few hundred ppm of H2 O, Cl, and F, which lowers the solidus and enhances the magma production rate. Adiabatic decompression melting in upwelling mantle plumes is the best explanation for young (last 200 Myr) volcanism on Mars. We explore water undersaturated mantle plume volcanism using a finite element mantle convection model coupled to a model of hydrous peridotite melting. Relative to a dry mantle, the reduction in solidus temperature due to water increases the magma production rate by a factor of 1.3–1.7 at 50 ppm water and by a factor of 1.9–3.2 at 200 ppm water. Mantle water also decreases the viscosity and increases the vigor of convection, which indirectly increases the magma production rate by thinning the thermal boundary layer and increasing the flow velocity. At conditions relevant to Mars, these indirect effects can cause an order of magnitude increase in the magma production rate. Using geologic and geophysical observations of the Late Amazonian magma production rate and geochemical observations of melt fractions in shergottite meteorites, present‐day Mars is constrained to have a core–mantle boundary temperature of 1750 to 1800 °C and a volume‐averaged thermal Rayleigh number of 2 × 10 6 to 10 7, indicating that moderately vigorous mantle convection has persisted to the present day. Melting occurs at depths of 2.5–6 GPa and is controlled by the Rayleigh number at the low pressure end and by the mantle water concentration at high pressure.